Mobile quantum gravity sensor with unprecedented stability. (June 2016) - Freier, C; Hauth, M; Schkolnik, V; Leykauf, B; Schilling, M; Wziontek, H; Scherneck, H-G; Müller, J; Peters, A
Abstract: Changes of surface gravity on Earth are of great interest in geodesy, earth sciences and natural resource exploration. They are indicative of Earth system's mass redistributions and vertical surface motion, and are usually measured with falling corner-cube- and superconducting gravimeters (FCCG and SCG). Here we report on absolute gravity measurements with a mobile quantum gravimeter based on atom interferometry. The measurements were conducted in Germany and Sweden over periods of several days with simultaneous SCG and FCCG comparisons. They show the best-reported performance of mobile atomic gravimeters to date with an accuracy of 39nm/s 2, long-term stability of 0.5nm/s 2 and short-term noise of 96nm/s 2 /√Hz. These measurements highlight the unique properties of atomic sensors. The achieved level of performance in a transportable instrument enables new applications in geodesy and related fields, such as continuous absolute gravity monitoring with a single instrument under rough environmental conditions.